2023
DOI: 10.1021/acs.joc.3c01306
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Catalyzed Hydroboration of Esters and Nitriles with Pinacolborane

Gobbilla Sai Kumar,
Ravi Kumar,
Abhijit Sau
et al.

Abstract: We developed a bench-stable iminopyridine-ligated zinc complex for the effective catalytic hydroboration of esters and nitriles under solvent-free conditions. Various esters and nitriles bearing different functionalities were selectively reduced to form corresponding alcohols and amines in good yields. Detailed Hammett plots are provided to explain the electronic effects on the phenyl ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…H ). 13 Authors also utilized commercially available zinc salts as catalysts. However, Schiff base stabilized zinc diiodide acts as a superior catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…H ). 13 Authors also utilized commercially available zinc salts as catalysts. However, Schiff base stabilized zinc diiodide acts as a superior catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Since Nikonov and coworkers discovered that a Mo(IV) complex could catalyse the hydroboration of nitriles in 2012, 32,33 research on the hydroboration of nitriles or alkynes has been increasing. A plethora of transition-metal complexes, such as zirconium, 34 manganese, 35 iron, 36,37 cobalt, 22,[38][39][40][41][42][43] nickel, [44][45][46] zinc, [47][48][49][50][51][52][53] ruthenium, [54][55][56] palladium, 57 and many rare-earth metal complexes, [58][59][60] can catalyse the hydroboration of nitriles or alkynes. In recent years, earth-abundant, nontoxic and inexpensive main group-metal compounds have become favourable catalysts in these research fields.…”
Section: Introductionmentioning
confidence: 99%
“…Recently zinc complexes have also started to gain the attention of researchers as potential catalysts for hydroboration reactions. 33–39 Yao et al and Mukherjee et al independently reported multidentate phenolate ligand-supported zinc alkyl complexes and N -heterocyclic carbine-based zinc complexes as catalysts for regioselective hydroboration of N -heteroarenes. 40,41 The Nembenna group established a conjugated bis-guanidinate zinc hydride complex as a catalyst for the hydroboration of isonitriles, nitriles and esters.…”
Section: Introductionmentioning
confidence: 99%